The association between pioglitazone consumption and incidence of bladder cancer in type II diabetic patients: a systematic review and meta-analysis of observational studies - Pantea Ramezannezhad; Mohammadreza Khosravifarsani (Society of Diabetic Nephropathy Prevention, 2023)
Background: Bladder cancer is the single most prevalent urinary tract malignancy in humans with a higher risk in diabetic patients. Pioglitazone is among the conventional antidiabetic drugs. The present study thus seeks to investigate the association between the administration of pioglitazone and the incidence of bladder cancer in type II diabetic patients through a meta-analysis and systematic analysis. Materials and Methods: International databases including Web of Science, Medline/PubMed, Scopus, and Google Scholar search engine were explored. To integrate the results of studies odds ratio (OR), risk ratio (RR) or hazard ratio (HR) logarithm was extracted from each study, and the I2 index or the Cochran's Q test were conducted to examine the heterogeneities across studies. Data analysis was carried out in STATA version14 considering a significance level of p<0.05. Results: The 15 examined studies had investigated a total of 5,353,528 patients (1,536,723 patients in case groups and 3,816,805 patients in control groups). The relative risk of bladder cancer was [RR: 1.20 (95% CI: 1.09-1.32)] in pioglitazone users. Bladder cancer risk in pioglitazone users was higher by [RR: 1.14 (95% CI: 1.03-1.25)] compared to those who had never taken pioglitazone, [RR: 1.32 (95% CI: 1.02-1.70] compared to sulfonylurea users, and [RR: 1.57 (95% CI: 1.23-2)] compared to dipeptidyl peptidase-4 (DPP-4) users. Moreover, the relative risk between pioglitazone consumption and bladder cancer was reported to be [RR: 1.27 (95% CI: 0.96-1.68)] in patients with a follow-up shorter than five years and [RR: 1.24 (95% CI: 1.09-1.41)] is patients with a follow-up of five years or longer. On the other hand, the relative risk between pioglitazone consumption and bladder cancer was [RR: 1 (95% CI: 0.69-1.45)] in 50-59 age group, [RR: 1.20 (95% CI: 1.04-1.38)] in the 60-69 age group, and [RR: 1.33 (95% CI: 1.14-1.56)] in the 70-79 age group. Conclusion: Patients who receive pioglitazone had a 20% higher risk of bladder cancer compared to those who had not taken pioglitazone or prescribed other medication such as sulfonylurea and DPP-4s. Registration: This study has been compiled based on the PRISMA checklist, and its protocol was registered on the PROSPERO website (ID: CRD42023391151).